(3GdcTchd ajeG LQi dGd GdQShds - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s
(3ChdgG (B:s
(3bd GdMeO ddg hSdGe Ydi YHGOg cJH Edi GYR GdfGS Ydi hGbQHge Rdai dOi GHO Gddg SYGOJg eG GhLH GdSDGd Yf eKd gPg GdGMhGd s
(3BNQgG (B:s
(3hbd cd jYed Ydi TGcdJg hSjYde GdPjf XdehG Edi Gi efbdH jfbdHhf hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3dYd GdeDda gh YHO Gddg Hf GdeYeGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B227s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B370s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs